Listening to the voices of teachers: primary physical education in Ireland. Issue 8 (2nd August 2020) - Murphy, Frances; McEvoy, Eileen
Abstract: This paper explores the life histories of 25 primary school teachers who had each taught for at least 25 years in Irish primary schools between 1972 and 2014. Specifically, the research explores the influences on their perspectives related to the nature and purpose of physical education. A qualitative methodological approach is employed, involving semi-structured interviews conducted by preservice teachers. The historical context of physical education in Ireland as well as literature related to socialisation frame the discussion of findings. Findings point to an absence of physical education in the teachers' personal experiences of primary education and an understanding of the purpose of physical education as related to health and physical activity. It is hoped that by providing accounts of teachers' lived experience of physical education both as learners and as teachers this paper will provide a valuable supplement to existing documentary evidence on the historical context and influences on physical education.